A qualitative investigation of company perspectives on online price discrimination. Issue 46 (September 2022) - Heidary, Kimia; Custers, Bart; Pluut, Helen; van der Rest, Jean-Pierre
Abstract: Online price discrimination (OPD) or personalized pricing has triggered many debates in the existing literature, due to its potential adverse effects on (trust in) markets and certain consumer groups. The implicit assumption underpinning these debates is the actual use of OPD in practice, although empirical research has not provided evidence of its common use. The aim of this study is to explore company perspectives regarding OPD and possible explanations as to why this practice is not widespread. Semi-structured interviews were held with 14 data scientists, sales managers, marketing directors and policy experts from Dutch companies. The findings indicate that companies are reluctant towards using OPD, particularly selective price increases. They rather seek other forms of data application for personalized marketing. Next to economic, technological, legal, and ethical considerations, consumer backlash was another key factor in the decision to engage in OPD. While companies do not seem convinced that the current regulatory initiatives are sufficiently effective, they support self-regulation and ethical codes. However, as more covert or indirect forms of OPD are expected, continued attention and scrutiny by regulators is warranted.